Pengaruh Komunikasi dan Kepemimpinan Terhadap Penyelesaian Konflik di Organisasi Kemahasiswaan (Senat, Himama, Himatha) Fakultas Bisnis Universitas Kristen Maranatha - Tarida Situmorang; Rusli Ginting Munthe (Eastasouth Institute, 2023)
The purpose of this research is to be able to determine the effect of communication and leadership on conflict resolution. Communication is one of the most important factors in the organization. Communication can make relationships better to avoid and overcome conflict. If there is a lack of communication, the organization is not functioning properly. The method used in this study uses quantitative methods. The population in this study were members of the senate, himama, and himatha business faculties of Maranatha Christian University. This study used a survey method with a sample of 88 respondents, sampling using the Now table. The data analysis technique used in this study used multiple linear regression analysis using SPSS. The results of this study indicate that communication and leadership have a positive influence on conflict resolution.